How Does Starbucks Develop Brand Loyalty Among Its Customers in Asia ? : Insights From Malaysia, Indonesia, and India - Kuek, Thiam Yong; Yusof, Rosmelisa; A/P Selvam, Sushmithaa; Binti Roslan, Siti Ramizah; A/L Aibau, Son Rakh; Su, Xinyi,; Vats, Isha; Singhal, Jahnavi; Chaudhary, Khushi; Kee, Daisy Mui Hung (The Global Academia Publisher, 2024)
Starbucks was founded in 1971 and is currently the world's largest chain coffee shop. Starbucks invaded Asian countries such as Malaysia, India and Indonesia a long time ago, and Asian countries have emerged as one of the most devoted customers. Brand loyalty is one of the most essential factors in increasing a company's revenue through customer retention. Starbucks' brand loyalty is influenced by several aspects, including pricing, products offered, product quality and taste. The purpose of this research is to determine how Starbucks develops brand loyalty among its customers in Malaysia, India and Indonesia. This survey will also be able to determine whether Asian customers will continue to be devoted Starbucks customers. The survey involved 136 people who are loyal Starbucks consumers from Malaysia, India and Indonesia. The data for this study was collected through online sources and questionnaires. We hope that this study will provide recommendations for increasing brand loyalty among our Asian customers, particularly in Malaysia, India, and Indonesia